The MSDIN family in amanitin-producing mushrooms and evolution of the prolyl oligopeptidase genes - Hong Luo; Qing Cai; Yunjiao Lüli; Xuan Li; Rohita Sinha; Heather E. Hallen-Adams; Zhu L. Yang (IMA Fungus)
Abstract The biosynthetic pathway for amanitins and related cyclic peptides in deadly Amanita (Amanitaceae) mushrooms represents the first known ribosomal cyclic peptide pathway in the Fungi. Amanitins are found outside of the genus in distantly related agarics Galerina (Strophariaceae) and Lepiota (Agaricaceae). A long-standing question in the field persists: why is this pathway present in these phylogenetically disjunct agarics? Two deadly mushrooms, A. pallidorosea and A. subjunquillea, were deep sequenced, and sequences of biosynthetic genes encoding MSDINs (cyclic peptide precursor) and prolyl oligopeptidases (POPA and POPB) were obtained. The two Amanita species yielded 29 and 18 MSDINs, respectively. In addition, two MSDIN sequences were cloned from L. brunneoincarnata basidiomes. The toxin MSDIN genes encoding amatoxins or phallotoxins from the three genera were compared, and a phylogenetic tree constructed. Prolyl oligopeptidase B (POPB), a key enzyme in the biosynthetic pathway, was used in phylogenetic reconstruction to infer the evolutionary history of the genes. Phylogenies of POPB and POPA based on both coding and amino acid sequences showed very different results: while POPA genes clearly reflected the phylogeny of the host species, POPB did not; strikingly, it formed a wellsupported monophyletic clade, despite that the species belong to different genera in disjunct families. POPA, a known house-keeping gene, was shown to be restricted in a branch containing only Amanita species and the phylogeny resembled that of those Amanita species. Phylogenetic analyses of MSDIN and POPB genes showed tight coordination and disjunct distribution. A POPB gene tree was compared with a corresponding species tree, and distances and substitution rates were compared. The result suggested POPB genes have significant smaller distances and rates than the house-keeping rpb2, discounting massive gene loss. Under this assumption, the incongruency between the gene tree and species tree was shown with strong support. Additionally, k-mer analyses consistently cluster Galerina and Amanita POPB genes, while Lepiota POPB is distinct. Our result suggests that horizontal gene transfer (HGT), at least between Amanita and Galerina, was involved in the acquisition of POPB genes, which may shed light on the evolution of the α-amanitin biosynthetic pathway.